Analytical gradients for electron-attached and ionized states for the algebraic-diagrammatic construction scheme for the electron propagator up to third order - Rehn, Dirk R.; Fink, Andreas; Dempwolff, Adrian; Dreuw, Andreas (The journal of physical chemistry. A, Molecules, clusters, and aerosols, 2024)
The derivation and implementation of analytical gradients for methods based on the non-Dyson algebraic diagrammatic construction for the electron propagator, IP-ADC and EA-ADC, up to the third order is presented. Using nuclear gradients, ground-state equilibrium structures for small open-shell systems are calculated. In addition, we investigated the performance of IP/EA-ADC methods for the calculation of adiabatic ionization potentials and electron affinities for medium-sized organic molecules.
Gesehen am 27.02.2025